Study of Hydrograf Synthetic Unit Method of Nakayasu, Limantara and Snyder on Way Semah - B Kurnia; Aprizal Aprizal; A Nurhasanah (Bandar Lampung University (UBL), 2017)
Way Semah River is the longest river located in Pesawaran Regency. Way Semah Creek passes several villages such as Gedong Tataan, Kesugihan, Kagungan Ratu, Katon Country, Halangan Ratu, Negara Saka, and many other villages. The upstream area of the Way Way River is located on Mount Pesawaran, while the downstream of the Way Semah River goes to the river Way Sekampung. The purpose of this study is to find out the fluctuation picture of the rising and falling water flow in the Way Semah river, knowing the peak discharge and the length of flow time, in certain period. The purpose of this study is to analyze rainfall occurring in das way semah. know the fluctuation of the water flow with the hydrograph of nakayasu, Limantara, and Snyder methods, and comparH Limantara, strongly influenced by the slope of the river, the higher the elevation difference between the upstream and downstream of the river, the higher the Qp value, and the reverse is true, whereas for the Tp value is relatively the same